Expert System for Diagnosing Strawberry Plant Diseases Using the Forward Chaining Method - Lavena, Deri; Rahmawati, Sri; Rahman, Sepsa Nur (Universitas Putra Indonesia YPTK Padang, 2025)
Farmers still do not really understand how to diagnose problems in plants, one example is strawberry farmers. This is proven by several farmers and strawberry plant cultivators, not all of whom can understand the disease where there are various types of diseases that can attack strawberry plants with almost the same symptoms , and if a farmer or cultivator is wrong in handling the type of strawberry plant disease, it is not impossible that it will cause the strawberry plant to die. Strawberry farmers need a tool to diagnose strawberry plant diseases so that they can find out the condition of the strawberry plants. Therefore, an expert system was created to diagnose diseases in strawberry plants and find solutions to deal with the damage that occurs. The system built for diagnosing diseases in strawberry plants uses the Forward Chaining method. Forward chaining is a forward tracking that starts from a set of facts by looking for rules that match the existing hypothesis towards a conclusion. In its implementation, this system has met these objectives by using a database and rule base. The system draws conclusions based on existing facts using the forward chaining method, the search starts from the facts from which new conclusions are obtained, the existing rules are traced one by one until the search is stopped because the last condition has been met.